Auditoría de costos al área de producción y su incidencia en la rentabilidad de la extractora Unipal S.A, recinto El Limón km 193 cantón Quinindé, periodo 2013 - Litardo Véliz, Karen Kaina (2015)
The present paper describes a type of Cost Audit was applied to an industrial company in the Quinindé, extractor UNIPAL SA, this research was conducted in a total of 83 working days during which the management of the company was measured looking include financial evaluation, assessment of existing controls needed to determine recommendations that benefit the audited company. Using the method, inductive, deductive, allowed to know the essential facts and how the industry is handled internally by applying analytical and synthetic method the physical area was observed and how it organizes the raw material in the yards of the extractor. Regarding the types of research used descriptive, bibliographic and field types of research that allowed us to meet the direct problems for the industry and finding the right documents for the required information faces, investigative techniques were also essential to obtain information directly from the manager, accountant and head of production, and observation to analyze the competitive field of the same. The run an audit to production costs and their impact on the profitability of the extractor UNIPAL SA Campus Lemon km 193, Quinindé, 2013 period, help other companies to have full knowledge of each step to take to thus the end of the accounting cycle have a real return. The findings made according to the results show that the company is facing serious problems in relation to the system of production costs, related to the three elements of cost, raw material, obtained 6% considered a finding of non-compliance, labor, breach 3% reflected as second finding and indirect manufacturing costs, with 2% with respect to the projection reflected as third finding. Given the completion of the research the results are reported to the manager by this corrective action and thus improve their management costs and extractor UNIPAL SA